SUN-LB111 Comparison of Phenotype and Metabolic Abnormalities Among Familial Partial Lipodystrophy Due to LMNA or PPARG Variants - Vasandani, Chandna (J Endocr Soc, 2020)
Familial partial lipodystrophy (FPLD), a rare autosomal dominant disorder, is characterized by marked loss of subcutaneous (sc) fat from the extremities, and predisposition to insulin resistance, diabetes mellitus, dyslipidemia and hepatic steatosis. FPLD2 and FPLD3 due to causal variants in LMNA and PPARG, respectively, are the two most common subtypes. Due to extremely rare prevalence of FPLD3 and limited reports in the literature, whether there are phenotypic differences between the two subtypes remain unclear. Therefore, we compared the anthropometric measurements and prevalence of metabolic abnormalities among 32 FPLD3 subjects (4 M, 28 F; mean ± SD age, 41 ± 17.2 y; body mass index (BMI), 26 ± 4.0 kg/m(2)) with 271 FPLD2 subjects (66 M, 205 F; age, 37.4 ± 17.0 y; BMI, 26 ± 5.0 kg/m(2)) from two referral centers in the United States. As compared to those with FPLD2, FPLD3 subjects had borderline higher prevalence of hypertriglyceridemia (66% vs 84%; P = 0.063), but significantly higher prevalence of diabetes (44% vs 72%; P = 0.004), past history of acute pancreatitis (13% vs 52%; P <0.001), and polycystic ovarian syndrome (26% vs 52%; P = 0.011). As compared to FPLD2, FPLD3 subjects had similar fasting triglyceride levels (median 208 vs 255 mg/dL; P=0.15), but lower high-density lipoprotein cholesterol levels (median 37.5 vs 30 mg/dL; P = 0.001), higher fasting glucose (median 95 vs 115 mg/dL; P = 0.05) and HbA1c (median 5.7 vs 7.0 %; P = 0.005) levels. Regional body fat was measured by dual energy X-ray absorptiometry in 19 FPLD3 and 105 FPLD2 subjects. In comparison to FPLD2, FPLD3 subjects had higher total fat (median 21.6% vs 26.1 %; P = 0.018); upper limb fat (median 20.3% vs 27.3%; P = 0.003) and lower limb fat (median 16.0% vs 20.8%; P = 0.007). Skinfold thickness measurements by calipers also revealed less severe fat loss from both the upper and lower extremities in FPLD3 subjects compared to FPLD2 subjects. As compared to FPLD2, FPLD3 subjects had significantly higher triceps skinfold thickness (median 5.5 mm vs 7.5 mm; P = 0.015); and thigh skinfold thickness (median 5.8 mm vs 11.3 mm; P = 0.001). There were no significant differences in the prevalence of fatty liver, plasma alanine aminotransferase and aspartate aminotransferase levels in the two subtypes. We conclude that compared to FPLD2 subjects, those with FPLD3 have milder lipodystrophy phenotype but paradoxically present with more severe metabolic complications, especially diabetes, dyslipidemia and polycystic ovarian syndrome. It is likely that this discrepancy could be due to early recognition of FPLD2 because of severe fat loss versus initial diagnosis of FPLD3 subjects due to severe metabolic complications leading to discovery of milder fat loss.